Spontaneous dislocation of lens bag with acrylic lens after uneventful cataract surgery – unusual complication of cataract surgery - Shah, Mehul A.; Shah, Shreya M.; Mehta, Ruchir; Shah, Prerna (GMS Ophthalmology Cases, 2015)
Introduction: Spontaneous dislocation of intraocular lens with bag is rare.Methods: We report a case of a 56-year-old male who presented with spontaneous anterior dislocation of an in-the-bag intraocular lens after manual small incision cataract surgery. He had undergone manual small incision cataract surgery with foldable acrylic intraocular lens implantation, and 18 months after cataract surgery ND: YAG capsulotomy with uneventful post capsulotomy follow-up. 17 months after capsulotomy, the patient presented with sudden decrease of vision. On anterior segment examination, the intraocular lens with bag was dislocated into the anterior chamber.Result: It was managed with intraocular lens explantation with bag, anterior vitrectomy and sclera fixated intraocular lens.Conclusion: Spontaneous intraocular lens dislocation with bag is possible after 1.5 years of uneventful surgery which may be managed using different techniques.